ANALISIS PENGUKURAN KINERJA SUPPLY CHAIN MANAGEMENT (SCM) TERHADAP KINERJA DAN DAYA SAING PADA CV POLACINDO BEKA - Firza Faturahman (LP2M Universitas Bina Bangsa, 2021)
In terms of business development, both individual companies and legal entities cannot avoid the performance of supply chain management and information strategies to be able to promote the development of the company itself. The purpose of this study is to examine how the performance of supply chain management and how information strategy CV Polacindo Beka in the company. Lots of food in Manado. What is done is the translation of achievements or work results. Even if the information is news or news. Information also This is real information or material that can be used as a basis for analysis and research or conclusions. This learning is classified as a qualitative type using raw data from interviews and direct observations. The results of the study conclude that the performance of supply chain management and information strategy is good because there is a complete and effective information and communication interaction among the participants in terms of supply chain management performance and information strategy